Effectiveness of rhBMP-2 association to autogenous, allogeneic, and heterologous bone grafts - Gonzaga, Miliane Goncalves; Santos Kotake, Bruna Gabriela dos; Tocchini de Figueiredo, Fellipe Augusto; Feldman, Sara; Ervolino, Edilson [UNESP]; Gorita dos Santos, Maria Cecilia; Mardegan Issa, Joao Paulo (Wiley-Blackwell, 2019)
Proteins with osteoinductive potential, especially recombinant human bone morphogenetic protein (rhBMP)-2, have large effects on cell growth and their differentiation. The aim of this study was to assess repair of bone defects in rat calvaria with different types of grafts associated with rhBMP-2, through immunohistochemistry and micro computed tomography (CT) analyses. A total of 35 male Wistar rats were selected, each weighing similar to 250 g, with a waiting period of 6 weeks from the creation of the defect to the sacrifice, and divided into five groups (n = 7): autograft plus 5 mu g rhBMP-2 (AuG/BMP-2); allograft plus 5 mu g rhBMP-2 (AlG/BMP-2); xenograft (heterologous) plus 5 mu g rhBMP-2 (XeG/BMP-2); 5 mu g rhBMP-2 (BMP-2) and the control group (n = 7). The micro CT reveal that all groups associating different bone grafts with BMP-2 showed increased bone formation compared to the control. The immunostaining show that osteocalcin and bone sialoprotein were higher in groups with BMP-2 than control group; BMP was high expressed in AuG/BMP-2, AlG/BMP-2, and BMP-2; vascular endothelial growth factor (VEGF) was more expressed in groups with BMP-2; VEGF-R2 was low to moderate in AuG/BMP-2, XeG/BMP-2, and BMP-2, predominantly moderate in AlG/BMP-2 and low in the control; CD-31 was predominantly moderate in AuG/BMP-2, AlG/BMP-2, and XeG/BMP-2, low to moderate in BMP-2 and low in the control. The results revealed that rhBMP-2 improved bone repair when administered alone, or when associated with different bone grafts.
Keywords: bone repair; graft; immunohistochemistry; micro CT; rhBMP-2